Setting the course: aligning European Union marine pollution policy ambitions with environmental realities - Devriese, Lisa I.; Verleye, Thomas J.; Vlachogianni, Thomais; Maes, Thomas; Boteler, Ben; Del Savio, Linda; Booth, Andy M.; Kopke, Kathrin (Frontiers in Marine Science, 2025)
Pollution in coastal and marine waters is a global challenge that transcends national boundaries, affecting interconnected seas, the ocean and broader ecosystems. Addressing marine pollution requires policies that encompass not only the marine domain but the entire ecosystem, including human societies. Therefore, a comprehensive and integrated governance approach, linking land-based sources to marine environments, is essential for effective pollution management and mitigation. This study assesses the current environmental status of persistent, long-lasting and emerging pollutants (PCBs, excess nutrients, microplastics, PFAS, and underwater noise) and cumulative effects of pollution, and compares these with the set European Union (EU) environmental goals and ambitions. A systematic review of EU policy documents reveals that several targets are unclear, arbitrary, and often unattainable, limiting the effectiveness of current strategies. This paper presents five actionable recommendations to strengthen marine environmental policy, emphasizing the need for better alignment between EU ambitions and environmental realities. To enhance EU pollution policies, it is crucial to reinforce regulatory frameworks, ensure the effective enforcement of existing legislation, foster collaboration across sectors, and empower citizens and NGOs. Additionally, integrating health and pollution policies, ensuring public access to pollution data and knowledge, and establishing international leadership in pollution efforts are key for making informed decisions and achieving ambitious pollution reduction targets.